2013
DOI: 10.1016/j.healthpol.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare payment reforms across western countries on three continents: Lessons from stakeholder preferences when asked to rate the supportiveness for fulfilling patients’ needs

Abstract: Objective. To test the hypothesis that care typology -being complex and highly unpredictable versus being clear-cut and highly predictable -guides healthcare payment preferences of physicians, policy makers, healthcare executives, and researchers.Data Sources/Study Setting. We collected survey data from 942 stakeholders across Canada, Europe, Oceania, and the United States. Forty-eight international societies invited their members to participate in our study. Study Design.Cross-sectional analysis of stakeholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…We observed that the total utilities between stakeholder groups become more closely aligned in the new payment system, in the sense that the differences in total utility between physicians and policy makers diminish. This result is in contrast with the result of the more direct preference enquiry of Van Herck et al [12], which revealed that care payment preferences between the stakeholder groups appear to be misaligned. There is thus a discrepancy in preferences that stakeholders directly state and those that are indirectly derived from a DCE.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…We observed that the total utilities between stakeholder groups become more closely aligned in the new payment system, in the sense that the differences in total utility between physicians and policy makers diminish. This result is in contrast with the result of the more direct preference enquiry of Van Herck et al [12], which revealed that care payment preferences between the stakeholder groups appear to be misaligned. There is thus a discrepancy in preferences that stakeholders directly state and those that are indirectly derived from a DCE.…”
Section: Resultscontrasting
confidence: 87%
“…In Eastern Europe and the US, this seems to be already the case. In addition, the findings confirm a closer alignment between stakeholder groups as a result of new payment structures, which is opposite to the result of the preference rating study of Van Herck et al [12], in which stakeholder preferences were directly enquired.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The knowledge base provided by SNL in EHRs provides opportunities to discover the nature of nursing care expenses. Employing SNL can encourage hospital leaders to increase documentation quality by focusing on the procedures and content of documentation (Van Herck et al., ). Standardized nursing diagnoses, intervention, and outcome data can be used for further prevalence studies, retrospective quality analyses, safety assurance strategies, and financial controlling (Keenan & Yakel, ; Keenan et al., ; Keenan, Yakel, Yao, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors asserted that the single payment method, such as only FFS, would not result in the optimal quantity of health services. The research of Van Herck et al 32 showed that physicians preferred payment systems that increased their benefits. Thus, it would be challenging to reform a payment system that did not reward the work of physicians.…”
Section: Comparison Of the Findings In This Study With Findings In The Existing Literaturementioning
confidence: 99%